The influence of continuous 100 pitches on extremities and trunk motions in basebal throwing kinematics - Inoue, N.; Watanabe, H.; Torii, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Shoulder and elbow injuries in baseball players have been reported many previous studies. One of the causative factors of the injuries have been expressed by a large number of pitching in game or practice .The purpose of this study was to compare baseball throwing kinematics before and after continuous 100 pitches and to investigate correlation between kinematic variations of extremities and trunk motions. METHODS: Ten collegiate baseball players (baseball history 8.7 ± 3.1y, ball speed 103 ± 7.3 km/h, age 21.5 ± 1.1y, height 175.6 ± 5.2cm, weight 70.8 ± 9.8kg) participated in this study. At first, reflective markers were placed at 11 bony landmarks. Then, we collected 3D coordinates of the points during throwing motion by using a 4-high speed camera of 300Hz and 3D digitizing system (Frame-Dias ‡W) before and after continuous 100 pitches. From those data, angles and angular velocities of shoulder, elbow, trunk, pelvic and thigh from foot contact (FC) to ball release (BR) were calculated. A statistics analysis of variance (P <.05) was used to compare the kinematic variables before and after continuous 100 pitches. RESULTS: Significant increase was observed in maximum shoulder external rotation angle (MER-A), maximum shoulder internal rotation angular velocity (Max SIR-V) during acceleration phase (AC), elbow extension angle (EE-A) at MER and BR, and thigh horizontal angle (TH-A) at FC after continuous 100 pitches compared with before. Moreover, there was a significant decrease in shoulder external rotation angle (ER-A) at BR and maximum elbow extension angle velocity (Max EE-V) during AC. On the other hand, trunk and pelvic kinematic variables showed no significant differences. There was no significant correlation between TH-A at FC and the upper extremity variables, either. DISCUSSIONS: The significant increase of MER-A, Max SIR-V during AC, and EE-A at MER and decrease of ER-A at BR passively induce higher throwing injury risk after continuous 100 pitches. Moreover, it is thought that the increase of TH-A at FC changed throwing motion to inside step. There was no significant correlation between TH-A at FC and the upper extremity variables, thus, TH-A at FC on inside had no influence on upper extremity motions as pelvic and trunk motions doesnt changes.